331 Effects of on-Arrival Application of a Modified-Live Respiratory and Clostridia Vaccination on Health, Growth Performance, and Antibody Titers of Newly Weaned Calves. (21st September 2022) - Gubbels, Erin R; Francis, Forest L; Rusche, Warren C; Smith, Zachary K
Abstract: The objective of this research was to evaluate health, growth performance, and antibody titers to IBR, BVD 1 and 2, PI3, and BRSV for calves administered a respiratory and clostridia vaccine compared with no vaccination upon arrival. Single-sourced, newly weaned steers (n = 70; initial body weight (BW) = 254±5.9 kg) were allotted to 10 pens (n = 5 pens/treatment with 7 steers/pen). Steers were blocked by BW in a RCBD of VAC (vaccinated for IBR, BVD 1 and 2, PI3, and BRSV and clostridial upon arrival) or NOVAC (not vaccinated upon arrival). Steers were individually weighed on d 0 (arrival), 1, 21, and 42 for growth performance measures. Whole blood samples were collected (n = 3 steers/pen closest to the pen mean BW) on d 1, 21, and 42 via jugular venipuncture for antibody titer responses. Depression scores of 0 (normal) to 4 (moribund) were recorded for each individual steer for 21 d. Body weight gain and feed efficiency were not influenced (P ≥ 0.10) by treatment. However, dry matter intake tended (P < 0.07) to increase as a percentage of BW by 3.5% for NOVAC compared with VAC. No treatment by day interactions (P > 0.05) were observed for depression scores or BVD 1 and 2 or PI3 titers. However, a treatment by day interaction (P < 0.03) was observed for IBR and BRSV titers. VAC steers had decreased (P < 0.05) titers for both IBR and BRSV on d 1 compared with d 21 but were similar (P > 0.05) to d 42, which were also similar (P > 0.05) to d 21 titers. Additionally, VAC steers had a 27% increase (P < 0.03) in PI3 titers compared with NOVAC steers. Collectively, growth performance was unaffected by vaccination, and vaccinated calves had increased antibody titer responses, as expected.